Coating of corrosion-resistant thermocouple for garbage power generation and preparation method of coating
By applying a composite coating structure on the thermocouple metal protective sleeve, combined with Al-Ni intermetallic compounds, cermet composite materials and nickel-based self-fusion alloys, the problem of insufficient resistance to high temperature, corrosion and wear resistance in waste incineration power generation environments is solved, and the service life is significantly extended.
Patent Information
- Application Number
- CN202411713506.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
Existing thermocouples have problems with insufficient high temperature resistance, corrosion resistance and wear resistance in waste incineration power generation environments, resulting in short service life.
The composite coating structure is adopted for transition layer and functional layer. The transition layer is composed of Al-Ni intermetallic compounds, cermet composite materials and high-expanded alloys. The functional layer is composed of nickel-based self-fusion alloys, ZrO2, ZrC, SiO2, Al2O3, Y2O3 coated WO3 composite materials and inorganic nanocomposite adhesives.
It significantly improves the high temperature, corrosion and wear resistance of the thermocouple metal protective sleeve, and extends the service life of the thermocouple in high temperature environments.
Smart Images

Figure CN119529567A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a coating of a corrosion-resistant thermocouple for waste-to-energy generation and a preparation method thereof. Background Art
[0002] Thermocouples are mainly composed of thermocouples, insulating tubes, metal protective sleeves and junction boxes. Among them, the thermocouples and insulating tubes are placed in metal protective sleeves to protect and support the thermocouples. Thermocouples can directly measure temperature and convert temperature signals into thermoelectric potential signals, which are further converted into the temperature of the measured medium through electrical instruments. In waste incineration power plants, thermocouples are widely used for temperature measurement in key areas such as furnaces and flues. Since the flue gas generated during waste incineration is hot and corrosive, and is mixed with a large amount of slag, ash and dust, thermocouples need to have excellent high temperature resistance, corrosion resistance and wear resistance.
[0003] By brushing or spraying ceramic coating on the surface of the thermocouple metal protective sleeve, the corrosion resistance of the thermocouple can be improved to a certain extent. However, the problems of poor adhesion, insufficient corrosion resistance and low hardness of the coating in the prior art seriously restrict the further development of the coating.
[0004] Chinese patent CN114645269B discloses a high-temperature resistant ceramic coating for thermocouples used in waste incinerators and its preparation method. By adding ceramic aggregates, boron nitride-coated titanium particles and flaky aluminum powder and other ingredients, the physical and chemical effects between the components are fully utilized to form a dense high-temperature resistant coating. However, the thermal expansion coefficient of the high-temperature resistant coating and the metal protective sleeve of the thermocouple is quite different, which makes the coating easy to expand and crack, reducing the service life of the thermocouple; Chinese patent CN115572934A discloses an anti-corrosion and wear-resistant composite coating applied to the heating surface of a waste incineration power generation boiler. The mechanical pinning effect formed enhances the bonding strength between the transition layer and the ceramic surface layer, thereby ensuring the coating quality. Ceramic coating as a surface layer not only increases the erosion resistance of the coating, improves the service life of the boiler pipeline, but also has electrochemical protection and physical shielding effects. However, the ceramic surface layer uses conventional erosion-resistant materials with low hardness and cannot withstand the erosion of high temperature and corrosive substances, resulting in easy wear and damage to the coating.
[0005] Therefore, how to simultaneously improve the high temperature resistance, corrosion resistance and wear resistance of the metal protective sleeve of the thermocouple used for waste-to-energy, thereby increasing the service life of the thermocouple at high temperatures, is a technical problem that urgently needs to be solved. Summary of the invention
[0006] The present application provides a corrosion-resistant thermocouple coating for waste-to-energy and a preparation method thereof to solve the following technical problem: how to simultaneously improve the high temperature resistance, corrosion resistance and wear resistance of the metal protective sheath of the thermocouple for waste-to-energy.
[0007] In a first aspect, the present application provides a coating of a corrosion-resistant thermocouple for waste-to-energy, the coating comprising:
[0008] A transition layer, the transition layer is attached to the surface of the thermocouple metal protection sleeve, and the coating of the transition layer is composed of the following chemical components by weight: 40 to 60 parts of Al-Ni intermetallic compound, 20 to 40 parts of metal ceramic composite material, and 10 to 20 parts of high expansion alloy; and
[0009] The functional layer is attached to the surface of the transition layer. The coating of the functional layer is composed of the following chemical components by weight: 20 to 50 parts of nickel-based self-fluxing alloy, 5 to 10 parts of ZrO2, 2 to 7 parts of ZrC, 5 to 10 parts of SiO2, 2 to 8 parts of Al2O3, 5 to 10 parts of Y2O3-coated WO3 composite material, 5 to 10 parts of inorganic nanocomposite binder, 1 to 3 parts of dispersant and 20 to 50 parts of solvent.
[0010] Optionally, the nickel-based self-fluxing alloy includes one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5; and / or,
[0011] The high expansion alloy includes one or more of Cu60Zn40, FeNi22Cr3, FeNi20Mn6, FeNi13Mn7 and Mn72Cr18Ni10.
[0012] Optionally, the inorganic nanocomposite binder includes one or more of aluminum dihydrogen phosphate, silica sol, aluminum sol and modified high-temperature epoxy adhesive.
[0013] Optionally, the Y2O3-coated WO3 composite material is a core-shell structure, wherein the mass of Y2O3 is 1 to 10% of the total mass of the Y2O3-coated WO3 composite material.
[0014] Optionally, the metal-ceramic composite material is composed of alumina-based metal-ceramic and silicon nitride-based metal-ceramic, and the mass ratio of the alumina-based metal-ceramic to the silicon nitride-based metal-ceramic is 1:(1-3).
[0015] Optionally, the thickness of the transition layer is 40 to 80 μm, and the thickness of the functional layer is 50 to 200 μm.
[0016] Optionally, the coating meets the following properties: microhardness HV ≥ 600, porosity < 0.5%, and service life of the thermocouple at 1300° C. > 180 d.
[0017] In a second aspect, the present application provides a method for preparing a coating according to any one embodiment of the first aspect, the preparation method comprising:
[0018] Shot peening of the thermocouple metal protection sleeve;
[0019] Spraying a transition layer coating onto the surface of the thermocouple metal protection sleeve to form a transition layer on the surface of the thermocouple metal protection sleeve;
[0020] The coating of the functional layer is applied to the surface of the transition layer, and then a curing treatment is performed to form the functional layer on the surface of the transition layer.
[0021] Optionally, the method for preparing the coating of the functional layer includes:
[0022] Ball milling SiO2 and Al2O3, adding an inorganic nanocomposite binder, and continuing the ball milling to obtain a first mixture;
[0023] Ball milling the nickel-based self-fluxing alloy, ZrO2, ZrC, a dispersant and a solvent to obtain a second mixture;
[0024] The first mixture, the second mixture and the Y2O3-coated WO3 composite material are mixed to obtain the coating of the functional layer.
[0025] Optionally, the preparation method of the Y2O3-coated WO3 composite material includes:
[0026] Dissolve Y2O3 in dilute nitric acid to obtain a mixed solution;
[0027] Impregnating WO3 in the mixed solution, and then performing solid-liquid separation to obtain a precursor;
[0028] The precursor is subjected to high temperature calcination to obtain a Y2O3-coated WO3 composite material; the temperature of the high temperature calcination is 900-1000°C, and the time of the high temperature calcination is 60-180 minutes.
[0029] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0030] The present application provides a coating for corrosion-resistant thermocouples for waste power generation. First, a composite coating structure of a transition layer and a functional layer is adopted. The transition layer mainly plays the role of enhancing the bonding force between the functional coating and the metal protective sleeve. The various components of the functional layer can form a multi-level protection, effectively isolating the contact between the corrosive medium and the thermocouple metal protective sleeve; secondly, the composition of the coating of the transition layer is reasonably designed. The Al-Ni intermetallic compound and the metal-ceramic composite material in the transition layer significantly enhance the bonding force between the coating and the metal protective sleeve through the synergistic effect at the molecular level, and effectively alleviate the problem of coating shedding caused by the difference in thermal expansion coefficient; thirdly, the chemical composition of the coating of the functional layer is reasonably designed, and the components such as nickel-based self-fluxing alloy, ZrO2, and ZrC form a stable metal-ceramic composite structure, which improves the hardness and wear resistance of the coating. At the same time, components such as SiO2, Al2O3 and Y2O3 coated WO3 composite materials form a dense oxide network structure, which enhances the corrosion resistance and high temperature resistance of the coating. In addition, the inorganic nanocomposite binder combines the components tightly together through a tight bonding effect, thereby improving the overall strength and toughness of the coating. The dispersant ensures the uniform dispersion of the various components in the coating, avoids the occurrence of agglomeration and precipitation, and thus improves the uniformity and stability of the coating; finally, through the combined effect of the composite coating structure of the transition layer and the functional layer, the reasonable design of the composition of the coating of the transition layer, and the reasonable design of the chemical composition of the coating of the functional layer, the high temperature resistance, corrosion resistance and wear resistance of the thermocouple metal protective sheath used for waste-to-energy are simultaneously improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0033] Figure 1 A schematic diagram of a corrosion-resistant thermocouple coating for waste-to-energy provided in an embodiment of the present application;
[0034] Figure 2 A flow chart of a method for preparing a corrosion-resistant thermocouple coating for waste-to-energy provided in an embodiment of the present application;
[0035] Reference numerals:
[0036] 1-thermocouple metal protection sleeve substrate, 2-transition layer, 3-functional layer. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0039] Figure 1 A schematic diagram of a corrosion-resistant thermocouple coating for waste-to-energy provided in an embodiment of the present application.
[0040] The present application provides a corrosion-resistant thermocouple coating for waste power generation, such as Figure 1 As shown, the coating comprises:
[0041] A transition layer, the transition layer is attached to the surface of the thermocouple metal protection sleeve, and the coating of the transition layer is composed of the following chemical components by weight: 40 to 60 parts of Al-Ni intermetallic compound, 20 to 40 parts of metal ceramic composite material, and 10 to 20 parts of high expansion alloy; and
[0042] The functional layer is attached to the surface of the transition layer. The coating of the functional layer is composed of the following chemical components by weight: 20 to 50 parts of nickel-based self-fluxing alloy, 5 to 10 parts of ZrO2, 2 to 7 parts of ZrC, 5 to 10 parts of SiO2, 2 to 8 parts of Al2O3, 5 to 10 parts of Y2O3-coated WO3 composite material, 5 to 10 parts of inorganic nanocomposite binder, 1 to 3 parts of dispersant and 20 to 50 parts of solvent.
[0043] The present application improves the high temperature resistance, corrosion resistance and wear resistance of the thermocouple metal protective sleeve used for waste-to-energy generation through the combined effect of the composite coating structure of the transition layer and the functional layer, the reasonable design of the coating composition of the transition layer, and the reasonable design of the chemical composition of the coating of the functional layer. The details are as follows:
[0044] 1. First, the present application adopts a composite coating structure of a transition layer and a functional layer. The transition layer is attached to the surface of the thermocouple metal protective sleeve, which mainly plays the role of enhancing the bonding force between the functional coating and the metal protective sleeve, while alleviating the problem of coating shedding caused by the difference in thermal expansion coefficient. The functional layer is attached to the surface of the transition layer and is the main functional part of the coating. It is responsible for withstanding various harsh conditions in the waste power generation environment. The various components in the functional layer can form a multi-level protection, effectively isolating the contact between the corrosive medium and the thermocouple metal protective sleeve, thereby improving the corrosion resistance of the coating.
[0045] Second, the present application rationally designs the composition of the coating of the transition layer. The functions of the chemical components of the coating of the transition layer are as follows:
[0046] Al-Ni intermetallic compounds: (1) Al-Ni intermetallic compounds are compounds formed by two metal elements, aluminum (Al) and nickel (Ni), in a specific atomic ratio and arrangement. The atoms in these compounds are connected to each other by metallic bonds, forming a stable crystal structure. When Al-Ni intermetallic compounds are used as part of the transition layer coating, their metallic bonds can form chemical bonds with the metal atoms on the surface of the metal protective sleeve, thereby enhancing the bonding between the coating and the metal protective sleeve. (2) Al-Ni intermetallic compounds generally have good wettability and spreadability, which means that they can evenly cover the surface of the metal protective sleeve to form a continuous coating. Good wettability and spreadability help increase the contact area between the coating and the metal protective sleeve, thereby further improving the bonding strength.
[0047] Metal-ceramic composites: (1) Metal-ceramic composites are composites composed of metal phases and ceramic phases. In the transition layer, the metal phase serves as the matrix, while the ceramic phase (such as oxides, carbides, etc.) serves as the reinforcing phase. The ceramic phase has excellent properties such as high hardness, high wear resistance and high corrosion resistance. When they are dispersed in the metal matrix in the form of tiny particles, they can be tightly bonded to the metal matrix through physical and chemical reactions to form a strong interface bond. (2) There is usually a difference in the thermal expansion coefficients of metals and ceramics. In the transition layer, by reasonably adjusting the ratio and distribution of the metal phase and the ceramic phase, the overall thermal expansion coefficient of the transition layer can be adjusted to a certain extent. When the thermal expansion coefficient of the transition layer is close to that of the metal protective sleeve, the problem of coating shedding caused by the difference in thermal expansion can be significantly reduced.
[0048] High expansion alloy: The addition of high expansion alloy is mainly to adjust the thermal expansion coefficient of the coating to make it more compatible with the substrate material, thereby reducing stress and peeling caused by thermal expansion mismatch.
[0049] The chemical components of the transition layer coating have significant synergistic effects, as follows:
[0050] (1) Enhanced bonding: The chemical bonding and wettability of the Al-Ni intermetallic compound, as well as the strong bonding between the reinforcing phase and the matrix in the metal-ceramic composite material, together enhance the bonding between the coating and the metal protective sleeve. This enhanced bonding makes the coating less likely to fall off in harsh working environments, thereby improving the stability and service life of the thermocouple. (2) Relieve thermal expansion differences: By adjusting the thermal expansion coefficient of the transition layer, it can be matched with the thermal expansion coefficient of the metal protective sleeve, thereby effectively alleviating the problem of coating shedding caused by thermal expansion differences. This mitigation effect further improves the stability and reliability of the coating, ensuring the normal operation of the thermocouple in high temperatures and harsh environments.
[0051] Therefore, the Al-Ni intermetallic compound and metal-ceramic composite material in the transition layer significantly enhance the bonding force between the coating and the metal protective sleeve through the synergistic effect at the molecular level, and effectively alleviate the problem of coating shedding caused by the difference in thermal expansion coefficient. This synergistic effect provides a strong guarantee for the stable operation of thermocouples in harsh environments such as waste power generation.
[0052] Third, the chemical composition of the functional layer coating should be reasonably designed. The functions of the chemical components of the functional layer coating are as follows:
[0053] Nickel-based self-fluxing alloy: Nickel-based self-fluxing alloy is mainly composed of nickel (Ni) and other alloying elements (such as chromium, silicon, boron, etc.). During the curing process of the coating, these elements are connected to each other through metallic bonds to form a stable alloy structure. Nickel has good ductility and corrosion resistance, and can maintain the stability and integrity of the coating in harsh environments. Other elements in the alloy, such as chromium, can enhance the high temperature resistance of the coating, while elements such as silicon and boron help to improve the hardness and wear resistance of the coating.
[0054] ZrO2 and ZrC: ZrO2 (zirconium dioxide) and ZrC (zirconium carbide) are both high-hardness ceramic materials with excellent wear resistance and high temperature resistance. In the coating, the molecules of ZrO2 and ZrC are connected to each other through ionic bonds or covalent bonds to form a dense ceramic network structure. This structure can effectively resist wear and scratches while maintaining the stability of the coating at high temperatures.
[0055] SiO2 and Al2O3: SiO2 (silicon dioxide) and Al2O3 (aluminum oxide) are both common inorganic oxides with good corrosion resistance and high temperature resistance. In the coating, the molecules of SiO2 and Al2O3 are bonded to the surrounding metal or ceramic molecules through ionic bonds or covalent bonds to form a stable compound structure. These compound structures can resist the erosion of various corrosive media while maintaining the stability of the coating at high temperatures. At the same time, under high temperature conditions, the molecules of SiO2 and Al2O3 are connected to each other through ionic bonds or covalent bonds to form a stable mullite structure. Mullite has a dense structure and low porosity, and can effectively resist the erosion of various corrosive media.
[0056] Y2O3 coated WO3 composite material: Y2O3 (yttrium oxide) as a coating material can significantly improve the high temperature resistance and stability of WO3 (tungsten trioxide). In the coating, Y2O3 molecules are combined with WO3 molecules through ionic bonds or covalent bonds to form a stable composite material structure. This structure can further enhance the high temperature resistance of the coating and improve its antioxidant ability.
[0057] Inorganic nanocomposite binder: Inorganic nanocomposite binder is composed of nano-scale inorganic particles and binder, and has excellent bonding performance and toughness. In the coating, inorganic nanoparticles combine with the surrounding metal, ceramic or oxide molecules through physical and chemical effects to form a tight bonding structure. This structure can significantly improve the overall strength and toughness of the coating, while enhancing the synergy between the components.
[0058] Dispersant: A dispersant is a surfactant that reduces the surface tension between the components in the coating and makes them dispersed evenly in the solvent. During the coating preparation process, dispersant molecules adsorb on the surface of the coating particles to form a protective film to prevent the particles from agglomerating and settling. This effect ensures that the coating forms a uniform coating structure during the curing process, thereby improving the overall performance of the coating.
[0059] The various chemical components of the functional layer coating jointly improve the high temperature resistance, corrosion resistance and wear resistance of the coating through complex interactions and synergistic mechanisms. The following is a detailed explanation of this synergistic effect:
[0060] Improved high temperature resistance. (1) Composite structure of metal and ceramic: Metal components such as nickel-based self-fluxing alloys provide good ductility and toughness, and can maintain the integrity of the coating at high temperatures. Ceramic components such as ZrO2 and ZrC have high melting points and can remain stable at extremely high temperatures to form a heat-resistant skeleton. (2) Stabilizing effect of oxide network: Oxide components such as SiO2 and Al2O3 can form a stable oxide network structure at high temperatures, effectively blocking the transfer of heat and improving the thermal insulation performance of the coating. The formation of mullite (generated by the reaction of SiO2 and Al2O3) further enhances the high temperature resistance of the coating. (3) Strengthening effect of inorganic nanocomposite binders: Inorganic nanocomposite binders tightly bind metal and ceramic components together through a tight bonding effect to form a stable composite structure, thereby improving the overall high temperature resistance of the coating.
[0061] Improved corrosion resistance. (1) The protective effect of the dense structure: The various components in the coating form a dense coating structure through chemical reaction and physical combination, which effectively blocks the corrosion of the corrosive medium on the substrate. Ceramic components such as ZrO2 and ZrC have excellent chemical stability and can resist the corrosion of a variety of corrosive media. (2) The barrier effect of the oxide layer: Oxide components such as SiO2 and Al2O3 can form a dense oxide layer at high temperature, which acts as a barrier to block the penetration of corrosive media. The formation of mullite further enhances this barrier effect and improves the corrosion resistance of the coating. (3) The strengthening effect of Y2O3-coated WO3 composite material: Y2O3-coated WO3 composite material can significantly improve the high-temperature oxidation resistance and corrosion resistance of the coating, and protect the coating from corrosion by forming a stable oxide layer.
[0062] Improved wear resistance. (1) Formation of hard phase: Ceramic components such as ZrO2 and ZrC have high hardness and can form hard phases in the coating, thereby improving the wear resistance of the coating. Hard carbides, borides, etc. in nickel-based self-fluxing alloys also enhance the wear resistance of the coating. (2) Synergistic effect of metal and ceramic: The metal component provides good toughness and ductility, which can absorb and disperse the impact force during wear. The ceramic component provides high hardness and wear resistance, which can resist friction and scratches during wear. (3) Bonding effect of inorganic nanocomposite binders: The inorganic nanocomposite binder firmly binds the components together through a tight bonding effect, forming a coating structure with excellent overall performance, thereby improving the wear resistance of the coating.
[0063] Therefore, components such as nickel-based self-fluxing alloy, ZrO2, and ZrC form a stable metal-ceramic composite structure, which improves the hardness and wear resistance of the coating. At the same time, components such as SiO2, Al2O3, and Y2O3-coated WO3 composite materials form a dense oxide network structure, which enhances the corrosion resistance and high temperature resistance of the coating. In addition, the inorganic nanocomposite binder combines the components tightly together through a tight bonding effect, which improves the overall strength and toughness of the coating. The dispersant ensures the uniform dispersion of the components in the coating, avoids the occurrence of agglomeration and precipitation, and thus improves the uniformity and stability of the coating. The components in the functional layer coating work synergistically at the molecular chemical level to jointly improve the high temperature resistance, corrosion resistance, and wear resistance of the coating, providing a strong guarantee for the stable operation of the thermocouple in harsh environments.
[0064] 4. Surface coating of thermocouple metal protective sleeve Under high temperature environment, the components in the coating will undergo a series of complex interactions and reactions, thus generating high temperature resistant and corrosion resistant coating materials. The following is a detailed description of these interactions and reactions:
[0065] Nickel-based self-fluxing alloy: (1) Nickel-based self-fluxing alloy will melt at high temperatures and react chemically with other components. As one of the main components of the coating, it can form a stable chemical structure with other oxides and composite materials. (2) The Ni element in the nickel-based self-fluxing alloy will react with oxides (such as ZrO2, SiO2, Al2O3) to form Ni oxides or composite oxides. These compounds have high stability and corrosion resistance at high temperatures.
[0066] Oxides (ZrO2, ZrC, SiO2, Al2O3): (1) At high temperatures, these oxides will undergo a certain degree of sintering and densification to form a more stable oxide layer. These oxide layers can effectively block the erosion of corrosive media and improve the corrosion resistance of the coating. (2) ZrO2 and ZrC have high hardness and wear resistance at high temperatures, which can further enhance the wear resistance of the coating. At the same time, they may also react chemically with other components (such as nickel-based self-fluxing alloys) to form new compounds or solid solutions. SiO2 and Al2O3 can enhance the chemical stability of the coating and prevent the coating from undergoing chemical changes at high temperatures. They will also interact with other components to form a more complex chemical structure.
[0067] Y2O3 coated WO3 composite material: (1) At high temperatures, Y2O3 in the Y2O3 coated WO3 composite material acts as a stabilizer to prevent WO3 from decomposing or changing phases at high temperatures. At the same time, WO3 has a certain catalytic effect, which can promote the formation of a dense oxide protective film on the coating surface. (2) Chemical reactions may occur between Y2O3 and WO3 to form new compounds or solid solutions. These compounds or solid solutions have high stability and corrosion resistance at high temperatures, which can further enhance the performance of the coating.
[0068] Inorganic nanocomposite binder: Inorganic nanocomposite binder will melt at high temperature and penetrate into the tiny gaps between the components to form a strong chemical bond. This binder can ensure that the components are tightly combined at high temperature to form a complete coating structure. At the same time, the nano-scale particle size enables the binder to more effectively fill and seal the tiny defects in the coating, improving the density and corrosion resistance of the coating.
[0069] Therefore, at a high temperature of 1200°C, complex interactions and reactions occur between the components in the transition layer and the functional layer. These reactions include processes such as interdiffusion, chemical reaction, sintering and densification. Through these processes, a tighter chemical bond and a more stable chemical structure are formed between the components. These structures make the coating have excellent high temperature resistance, corrosion resistance and wear resistance at high temperatures.
[0070] In some optional embodiments, the nickel-based self-fluxing alloy includes: one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5; and / or,
[0071] The high expansion alloy includes one or more of Cu60Zn40, FeNi22Cr3, FeNi20Mn6, FeNi13Mn7 and Mn72Cr18Ni10.
[0072] The nickel-based superalloy coating is dense, has high bonding strength, is resistant to corrosion and cavitation, can withstand high temperatures of 982°C, and has excellent oxidation resistance. It is used as a high-temperature heat-resistant coating and as a bonding transition layer for thermal barrier coatings. It is used for heat-resistant coatings on the surfaces of thermal equipment such as metallurgical rollers, hot-dip immersion rollers, and heat treatment furnace rollers; heat-resistant coatings for aircraft engine blades and gas turbine blades, as well as bonding transition layers for thermal barrier coatings on high-temperature furnace tuyere and heat shield surfaces.
[0073] In some optional embodiments, the particle size of the nickel-based self-fluxing alloy is -140M+325M; -325M.
[0074] In some optional embodiments, the inorganic nanocomposite binder includes one or more of aluminum dihydrogen phosphate, silica sol, aluminum sol and modified high-temperature epoxy adhesive.
[0075] It should be noted that aluminum dihydrogen phosphate is an inorganic adhesive with excellent fire resistance, flame retardancy and high-temperature bonding performance. It can maintain stable bonding strength in high temperature environments and is not easily oxidized or decomposed.
[0076] Silica sol is a dispersion of nano-sized silica particles in water or solvent. It has good dispersibility, permeability and adhesion. The silica particles in silica sol contain a large amount of water and hydroxyl groups, which enables it to form a strong silicon-oxygen bond when it loses water, making it a good adhesive.
[0077] Nano-alumina sol is a colloidal solution of positively charged feather-shaped aluminum oxide particles dispersed in water. It has adhesiveness, film-forming properties and heat resistance, and its solid components are almost entirely composed of aluminum oxide, so it has extremely high heat resistance.
[0078] After curing, epoxy adhesive is an amorphous, highly cross-linked material with the advantages of various curing methods, low shrinkage, good wettability, high corrosion resistance, good mechanical strength and adhesion, and appropriate chemical resistance and heat resistance.
[0079] In some optional embodiments, the Y2O3-coated WO3 composite material is a core-shell structure, wherein the mass of Y2O3 is 1 to 10% of the total mass of the Y2O3-coated WO3 composite material.
[0080] Y2O3 coated WO3 composite material is a material with a special core-shell structure, in which Y2O3 is the shell material and WO3 is the core material. This structure can improve its high temperature oxidation resistance, corrosion resistance and mechanical strength.
[0081] In some optional embodiments, the metal-ceramic composite material is composed of aluminum oxide-based metal ceramic and silicon nitride-based metal ceramic, and the mass ratio of the aluminum oxide-based metal ceramic to the silicon nitride-based metal ceramic is 1:(1-3).
[0082] The mass ratio of alumina-based cermets to silicon nitride-based cermets is 1:(1-3), which can significantly enhance the bonding force between the coating and the metal protective sleeve and effectively alleviate the problem of coating shedding caused by differences in thermal expansion coefficients. In addition, under high temperature conditions, thermal stress may be generated between the coating and the metal protective sleeve due to the inevitable difference in thermal expansion coefficients. The composite structure of alumina-based cermets and silicon nitride-based cermets can effectively disperse and alleviate these thermal stresses, thereby reducing the risk of coating shedding.
[0083] In some optional embodiments, the thickness of the transition layer is 40 to 80 μm, and the thickness of the functional layer is 50 to 200 μm.
[0084] In some optional embodiments, the coating meets the following properties: microhardness HV ≥ 600, porosity < 0.5%, and service life of the thermocouple at 1300° C. > 180 d.
[0085] Figure 2 A flow chart of a method for preparing a coating of a corrosion-resistant thermocouple for waste-to-energy provided in an embodiment of the present application.
[0086] Based on a general inventive concept, the present application provides a method for preparing a coating as described in any one of the above embodiments, such as Figure 2 As shown, the preparation method comprises:
[0087] S1. Shot peening the thermocouple metal protection sleeve;
[0088] The main purpose of shot peening is to pre-treat the surface of the thermocouple metal protection sleeve to enhance its surface roughness and adhesion. Through shot peening, tiny concave and convex structures can be formed on the surface of the sleeve, which helps the subsequent coating material to adhere better to the sleeve.
[0089] S2, spraying a coating of a transition layer onto the surface of the thermocouple metal protection sleeve to form a transition layer on the surface of the thermocouple metal protection sleeve;
[0090] The main function of the transition layer is to provide an intermediate layer between the thermocouple metal protection tube and the functional layer to alleviate the differences in thermal expansion coefficients, chemical incompatibility, etc. The transition layer can also enhance the overall strength and durability of the coating system.
[0091] S3, coating the coating of the functional layer on the surface of the transition layer, and then performing a curing treatment to form a functional layer on the surface of the transition layer.
[0092] The functional layer is the outermost layer of the coating system, which directly faces the working environment and plays the main protective and functional role. The functional layer can have a variety of properties, such as high temperature resistance, corrosion resistance, wear resistance, etc.
[0093] In some optional embodiments, the method for preparing the coating of the functional layer includes:
[0094] S101, ball-milling SiO2 and Al2O3, adding an inorganic nanocomposite binder, and continuing the ball-milling to obtain a first mixture;
[0095] S102, ball-milling the nickel-based self-fluxing alloy, ZrO2, ZrC, a dispersant and a solvent to obtain a second mixture;
[0096] S103, mixing the first mixture, the second mixture and the Y2O3-coated WO3 composite material to obtain the coating of the functional layer.
[0097] In the first mixture and the second mixture, a ceramic matrix composed of SiO2, Al2O3 and an inorganic nanocomposite binder, and a metal-ceramic composite system composed of a nickel-based self-fluxing alloy, ZrO2, ZrC, a dispersant and a solvent are formed respectively. When the first mixture, the second mixture and the Y2O3-coated WO3 composite material are mixed, the Y2O3 and WO3 in the molecules can chemically bond or physically adsorb with the molecules in the ceramic matrix and the metal-ceramic composite system to form a tighter bond. This combination not only improves the overall strength of the coating, but also gives the coating special high temperature resistance and corrosion resistance. Therefore, the three-step mixing preparation process ensures the uniform dispersion, tight bonding and improvement of special properties of the raw materials at the molecular level, thereby preparing a functional layer coating with excellent performance.
[0098] In some optional embodiments, the preparation method of the Y2O3-coated WO3 composite material includes:
[0099] S201, dissolving Y2O3 in dilute nitric acid to obtain a mixed solution;
[0100] S202, immersing WO3 in the mixed solution, and then performing solid-liquid separation to obtain a precursor;
[0101] S203, calcining the precursor at high temperature to obtain a Y2O3-coated WO3 composite material; the temperature of the high temperature calcination is 900-1000°C, and the time of the high temperature calcination is 60-180 minutes.
[0102] The preparation method of Y2O3 coated WO3 composite material realizes the uniform coating of Y2O3 on the surface of WO3 through three steps of dissolution, impregnation and high temperature calcination. This composite material combines the excellent properties of Y2O3 and WO3, such as high high temperature resistance, corrosion resistance and good mechanical properties, and has broad application prospects.
[0103] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0104] Example 1
[0105] This embodiment provides a corrosion-resistant thermocouple coating for waste-to-energy, the coating comprising:
[0106] A transition layer, the transition layer is attached to the surface of the thermocouple stainless steel protective sleeve, and the coating of the transition layer is composed of the following chemical components by weight: 50 parts of Al-Ni intermetallic compound, 30 parts of metal-ceramic composite material, and 20 parts of high expansion alloy;
[0107] Wherein, the Al-Ni intermetallic compound is Ni3Al, the metal-ceramic composite material is composed of an alumina-based metal ceramic and a silicon nitride-based metal ceramic in a mass ratio of 1:1, the model of the alumina-based metal ceramic is 96 porcelain (a ceramic material with an alumina content of about 96%), the model of the silicon nitride-based metal ceramic is YB-1, and the high expansion alloy is Cu60Zn40;
[0108] The functional layer is attached to the surface of the transition layer. The coating of the functional layer consists of the following chemical components in parts by weight: 34 parts of nickel-based self-fluxing alloy, 5 parts of ZrO2, 5 parts of ZrC, 10 parts of SiO2, 4 parts of Al2O3, 6 parts of Y2O3-coated WO3 composite material, 10 parts of inorganic nanocomposite binder, 1 part of dispersant and 25 parts of solvent.
[0109] Among them, the nickel-based self-fluxing alloy is NiCo23Cr17Al12Y0.5, the inorganic nano-composite binder is silica sol (Shandong Better New Materials, model S3010, content of 30%, particle size of 10-15nm sodium-type silica sol), in the Y2O3-coated WO3 composite material, the mass proportion of Y2O3 is 5%, the mass proportion of WO3 is 95%, the dispersant is sodium dodecyl sulfate, and the solvent is deionized water.
[0110] Based on the above coating, this embodiment also provides a method for preparing the coating, which specifically includes the following steps:
[0111] Step 1, dissolving Y2O3 in dilute nitric acid to obtain a mixed solution; immersing WO3 in the mixed solution, and then performing solid-liquid separation to obtain a precursor; calcining the precursor at high temperature to obtain a Y2O3-coated WO3 composite material; the high-temperature calcination temperature is 900°C, and the high-temperature calcination time is 180 minutes.
[0112] Step 2: Mix Al-Ni intermetallic compound powder, metal-ceramic composite material powder and high expansion alloy powder to obtain a coating for a transition layer.
[0113] Step 3: ball-milling SiO2 and Al2O3, adding an inorganic nanocomposite binder, and continuing the ball-milling to obtain a first mixture; ball-milling the nickel-based self-fluxing alloy, ZrO2, ZrC, a dispersant, and a solvent to obtain a second mixture; and mixing the first mixture, the second mixture, and the Y2O3-coated WO3 composite material to obtain the coating of the functional layer. The ball-milling time is 80 minutes.
[0114] Step 4: Use a sandblasting machine to spray steel shots of a certain size and speed onto the surface of the thermocouple metal protection sleeve; use a spray gun to evenly spray the coating of the transition layer onto the surface of the thermocouple metal protection sleeve to form a transition layer on the surface of the thermocouple metal protection sleeve; apply the coating of the functional layer to the surface of the transition layer, and then dry and cure to form a functional layer on the surface of the transition layer. The spraying temperature is 920°C, the thickness of the transition layer is 40 μm, and the thickness of the functional layer is 200 μm.
[0115] Example 2
[0116] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0117] The coating of the transition layer is composed of the following chemical components: 60 parts of Al-Ni intermetallic compound, 20 parts of metal-ceramic composite material, and 20 parts of high expansion alloy.
[0118] Example 3
[0119] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0120] The coating of the transition layer is composed of the following chemical components: 40 parts of Al-Ni intermetallic compound, 40 parts of metal-ceramic composite material, and 20 parts of high expansion alloy.
[0121] Example 4
[0122] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0123] The coating of the functional layer is composed of the following chemical components: 50 parts of nickel-based self-fluxing alloy, 5 parts of ZrO2, 2 parts of ZrC, 5 parts of SiO2, 2 parts of Al2O3, 5 parts of Y2O3-coated WO3 composite material, 5 parts of inorganic nanocomposite binder, 1 part of dispersant and 25 parts of solvent.
[0124] Example 5
[0125] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0126] The coating of the functional layer is composed of the following chemical components: 20 parts of nickel-based self-fluxing alloy, 9 parts of ZrO2, 6 parts of ZrC, 9 parts of SiO2, 8 parts of Al2O3, 10 parts of Y2O3-coated WO3 composite material, 10 parts of inorganic nanocomposite binder, 3 parts of dispersant and 25 parts of solvent.
[0127] Example 6
[0128] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0129] The metal-ceramic composite material is an alumina-based metal-ceramic.
[0130] Example 7
[0131] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0132] The metal-ceramic composite material is silicon nitride-based metal-ceramic.
[0133] Example 8
[0134] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0135] In the Y2O3 coated WO3 composite material, the mass proportion of Y2O3 is 10% and the mass proportion of WO3 is 90%.
[0136] Comparative Example 1
[0137] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0138] The coating of the transition layer does not contain Al-Ni intermetallic compounds.
[0139] Comparative Example 2
[0140] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0141] The coating of the transition layer does not contain any metal-ceramic composite material.
[0142] Comparative Example 3
[0143] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0144] The coating of the transition layer does not contain high expansion alloys.
[0145] Comparative Example 4
[0146] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0147] No ZrO2 is added to the coating of the functional layer.
[0148] Comparative Example 5
[0149] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0150] No ZrC is added to the coating of the functional layer.
[0151] Comparative Example 6
[0152] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0153] The coating of the functional layer does not contain SiO2 and Al2O3.
[0154] Comparative Example 7
[0155] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0156] No SiO2 is added to the coating of the functional layer.
[0157] Comparative Example 8
[0158] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0159] The coating of the functional layer does not contain Y2O3-coated WO3 composite material.
[0160] Comparative Example 9
[0161] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0162] The coating of the functional layer does not contain any inorganic nanocomposite binder.
[0163] Comparative Example 10
[0164] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0165] The 6 parts of Y2O3-coated WO3 composite material were replaced with 0.3 parts of Y2O3 and 5.7 parts of WO3 alone.
[0166] Comparative Example 11
[0167] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0168] The surface of the thermocouple metal protection sleeve is only provided with a functional layer, and no transition layer is provided.
[0169] Comparative Example 12
[0170] This embodiment is further modified as follows based on the content disclosed in Embodiment 1:
[0171] The surface of the thermocouple metal protection sleeve is not coated.
[0172] The surface coatings of the thermocouple metal protection sleeves of Examples 1 to 8 and Comparative Examples 1 to 12 were subjected to performance tests, and the results are shown in Tables 1 and 2. High temperature resistance test method: The thermocouple metal protection sleeve was placed in a high temperature furnace, heated to 1300°C for 1 hour, cooled with the furnace, and observed whether cracking or melting occurred on the surface of the coating. Adhesion was measured according to GB / T9286-1998. The time for the surface coating of the thermocouple metal protection sleeve to corrode to the substrate of the protection sleeve in 5% sulfuric acid and 5% sodium hydroxide solution was recorded.
[0173] Table 1 Performance of the surface coating of the thermocouple metal protection sleeve of Examples 1 to 8
[0174]
[0175]
[0176] As shown in Table 1, the surface coating microhardness of the metal protective sleeve of the thermocouple in Examples 1 to 8 is HV≥600, the porosity is <0.5%, the service life of the thermocouple at 1300°C is >180d, the time for corrosion to the protective sleeve substrate in 5% sulfuric acid solution is >3000h, and the time for corrosion to the protective sleeve substrate in 5% sodium hydroxide solution is >3100h. In Examples 6 and 7, the metal-ceramic composite material is a single metal-ceramic material, and the service life is slightly reduced.
[0177] Table 2 Performance of coating on the surface of thermocouple metal protection sleeve of comparative examples 1 to 12
[0178]
[0179] As shown in Table 2, in Comparative Examples 1 to 3, the coating of the transition layer lacks important components, resulting in reduced bonding between the functional coating and the thermocouple metal protection sleeve, and reduced corrosion resistance of the coating. Among them, Comparative Example 3 has the largest reduction. This is due to the lack of high expansion alloy, which causes the thermal expansion coefficient of the transition layer to be much lower than that of the thermocouple metal protection sleeve, and poor bonding. In Comparative Examples 4 to 10, the coating of the functional layer lacks important components, resulting in reduced production of high temperature resistant and corrosion resistant coating materials, reduced corrosion resistance, and Comparative Example 11 lacks a transition layer, resulting in poor bonding between the functional coating and the thermocouple metal protection sleeve, the coating is easy to fall off, and reduced corrosion resistance.
[0180] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0181] In the description of the specification of the present application, the terms "include", "comprise", etc. mean "including but not limited to". In this article, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A and B can be singular or plural. In this article, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple, respectively.
[0182] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features applied for herein.
Claims
1. A corrosion-resistant thermocouple coating for waste-to-energy, characterized in that: The coating comprises: A transition layer, the transition layer is attached to the surface of the thermocouple metal protection sleeve, and the coating of the transition layer is composed of the following chemical components by weight: 40 to 60 parts of Al-Ni intermetallic compound, 20 to 40 parts of metal ceramic composite material, and 10 to 20 parts of high expansion alloy; and The functional layer is attached to the surface of the transition layer. The coating of the functional layer is composed of the following chemical components by weight: 20 to 50 parts of nickel-based self-fluxing alloy, 5 to 10 parts of ZrO2, 2 to 7 parts of ZrC, 5 to 10 parts of SiO2, 2 to 8 parts of Al2O3, 5 to 10 parts of Y2O3-coated WO3 composite material, 5 to 10 parts of inorganic nanocomposite binder, 1 to 3 parts of dispersant and 20 to 50 parts of solvent.
2. The coating according to claim 1, characterized in that The nickel-based self-fluxing alloy includes one or more of NiCo23Cr17Al12Y0.5, NiCo23Cr20Al8.5Ta4Y0.1 and CoNi32Cr21Al8Y0.5; and / or, The high expansion alloy includes one or more of Cu60Zn40, FeNi22Cr3, FeNi20Mn6, FeNi13Mn7 and Mn72Cr18Ni10.
3. The coating according to claim 1, characterized in that The inorganic nano composite adhesive comprises: one or more of aluminum dihydrogen phosphate, silica sol, aluminum sol and modified high temperature epoxy adhesive.
4. The coating according to claim 1, characterized in that The Y2O3-coated WO3 composite material is a core-shell structure, wherein the mass of Y2O3 is 1-10% of the total mass of the Y2O3-coated WO3 composite material.
5. The coating according to claim 1, characterized in that The metal-ceramic composite material consists of aluminum oxide-based metal ceramic and silicon nitride-based metal ceramic, and the mass ratio of the aluminum oxide-based metal ceramic to the silicon nitride-based metal ceramic is 1:(1-3).
6. The coating according to claim 1, characterized in that The thickness of the transition layer is 40-80 μm, and the thickness of the functional layer is 50-200 μm.
7. The coating according to claim 1, characterized in that The coating meets the following properties: microhardness HV≥600, porosity<0.5%, and service life of the thermocouple at 1300°C>180d.
8. A method for preparing a coating according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Shot peening of the thermocouple metal protection sleeve; Spraying a transition layer coating onto the surface of the thermocouple metal protection sleeve to form a transition layer on the surface of the thermocouple metal protection sleeve; The coating of the functional layer is applied to the surface of the transition layer, and then a curing treatment is performed to form the functional layer on the surface of the transition layer.
9. The method according to claim 8, characterized in that The preparation method of the coating of the functional layer comprises: Ball milling SiO2 and Al2O3, adding an inorganic nanocomposite binder, and continuing the ball milling to obtain a first mixture; Ball milling the nickel-based self-fluxing alloy, ZrO2, ZrC, a dispersant and a solvent to obtain a second mixture; The first mixture, the second mixture and the Y2O3-coated WO3 composite material are mixed to obtain the coating of the functional layer.
10. The method according to claim 9, characterized in that The preparation method of the Y2O3-coated WO3 composite material comprises: Dissolve Y2O3 in dilute nitric acid to obtain a mixed solution; Impregnating WO3 in the mixed solution, and then performing solid-liquid separation to obtain a precursor; The precursor is subjected to high temperature calcination to obtain a Y2O3-coated WO3 composite material; the temperature of the high temperature calcination is 900-1000°C, and the time of the high temperature calcination is 60-180 minutes.
Citation Information
Patent Citations
High-temperature-resistant abrasion-resistant remelting nickel-based composite coating for fire grate segment of garbage incinerator and preparation of high-temperature-resistant abrasion-resistant remelting nickel-based composite coating
CN111876717A
Preparation method of high-temperature-chlorine-corrosion-resistant ceramic coating for red mud base material of incinerator
CN114736002A
Metal ceramic composite coating, corrosion-resistant incinerator superheater tube and preparation method
CN117070082A
High-temperature-resistant and anti-corrosion thermocouple
CN219573294U
Heating tube for boilers and method of manufacturing the same
US6082444A